The Future Climatic Variabilities in the Mano River Union, Its Implications on Socio-Economic Development - Solomon, Mahmoud; Abiodun, Oludayo Emmanuel; Olusina, Joseph Olalekan; Olaleye, James Bolarinwa (Geographica Pannonica, 2022)
Knowledge of climatic variability of any country or region is essential to socio-economic development. This is particularly important as most sectors of national development can be altered if the climatic conditions are unsuitable. A hypothetical case lies in the fact that agriculture largely depends on apposite climate for fruitful production. The Mano River Region consists of some of the world’s poorest and least developed nations (Guinea, Sierra Leone, Liberia, Cote D’Ivoire). The primary means of sustenance in this region is rain-fed agriculture. Knowledge of current and future climatic conditions in the region will be of significant benefit to the economy of the region. This work investigates the current and future state of climate in the region using six climatic parameters (Maximum and minimum temperature, Precipitation, Relative Humidity, Wind Speed and Solar Radiation) spanning 1975—2018. To model the impact/relationship, Kalman Filter was used. These variables were grouped into state transition and control variables. Transfer functions which depict relationships between every two variables at a time with one being input and the other considered as output were used to determine state transition and control variable matrices. Control variables (population and land use) were introduced to control the dynamism of the model in MATLAB environment. Results show that there is a drastic variation in climate in the region within the period of the data. This work establishes that there are rapid variabilities in these parameters which can be attributed to increase in population and loss of vegetation.